Digestibility of Nutrients as Influenced by Supplementation of Exogenous Fibrolytic Enzymes in Dry Non-pregnant Cows - Lunagariya, PM; Gupta, RS; Shah, SV; Patel, YG (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
The study was planned to evaluate the effect of exogenous fibrolytic enzymes (EFE) supplementation for 56 days @ 240 mg/kg total mixed ration (TMR) on digestibility of dry matter and nutrients in dairy cows. Six dry non-pregnant cows were assigned in each treatment with and without EFE. The digestibility trial of seven days was conducted after 49 days of feeding. Dry matter and nutrients intake of cows was not influenced by EFE. The supplementation of EFE had improved digestibility of dry matter, organic matter, crude fiber, neutral detergent fiber, cellulose (p <0.01), as well as digestibility of nitrogen-free extract and acid detergent fiber, was also higher (p<0.05). The body weight gain of cows was higher on the supplementation of EFE in TMR. The study concluded that feeding exogenous fibrolytic enzymes (240 mg/kg) supplemented TMR improved digestibility of dry matter and nutrients, which was reflected as higher body weight gain in dry non-pregnant Gir and crossbred dairy cows.